Effect of type of aggregate on ultrasonic pulse velocity of concrete - Ramakrishna, G.; Ramakrishna, B.; reddy, S. Sivamurthy; Narasimha, V. L. (Journal of Structural Engineering, 2025)
Aggregates such as granite, dolerite, quartzite, dolomitic limestone, limestone and river gravel were used to produce the concrete with 28-day target compressive strength of 35, 60 and 80 MPa. Petrographic characteristics, Physical properties, ultrasonic pulse velocity and compressive strength of aggregates were measured to study their effect on pulse velocity of concrete. Both compressive strength and pulse velocity of concrete made of same type of aggregate increased with grade of concrete. However, the same relationship was not observed in the concrete of same grade made of different types of aggregates. Crystalline aggregates with higher pulse velocities have imparted greater pulse velocity to concrete irrespective of strength of concrete. Concrete made of carbonate aggregates have exhibited higher pulse velocity than concrete with non-carbonate aggregates though the pulse velocity of carbonate aggregates are less than crystalline aggregates. The mode of origin, ultrasonic pulse velocity, texture and mineralogical composition of aggregates has profound impact on the pulse velocity of concrete.